Modelling inflation in the Philippines the P-Star model approach - Habibullah, Muzafar Shah; Smith, Peter (The Philippine Review of Business and Economics, 1998)
The P-Star approach of modelling inflation has been widely tested for the United States and other developed countries. However, the robustness of the P-Star model for developing countries has received less attention among the researchers. The purpose of this study is to test the applicability of the P-Star approach with respect to a developing country - the Philippines. Using a sample period of 1981:1 to 1994:4, our results suggest that the monetary data for the Philippines support the P-Star model approach. Our results indicate that broad money M2 provides an anchor for the Philippines inflation during the period under study.